Disfunción endotelial. Mecanismos e implicancias en Covid-19 - Maldonado C, Felipe; Valdés A, Catalina; Díaz P, Catalina; Valls J, Nicolás; Romero P, Carlos; Cerda A, Óscar; Cáceres Ll, Mónica (Revista Hospital Clínico Universidad de Chile, 2021)
Endothelium is the inner layer of vessels that separates circulating blood from the rest of the body tissues. Since its discovery, it has been involved in various functions, both systemic and organ specific. Currently, endothelial damage and failure in its functions is considered a key element in pathophysiology of various clinical scenarios, among which we may find COVID-19. Hence, it has been a target in development of strategies that seek to maintain, enhance or repair its function. The purpose of the following review is to describe what an endothelial function is about, its relation with current medical practice, and its implications in the SARSCoV-2 pandemic.